Public Service as an Employer of Choice: Study of Problems or Challenges Faced by National Bank of Pakistan with Respect to Recruitment and Retention - Aslam, Sumaira; Mahmood, Babak; Hafeez, Saima; Hussain, Shabbir (Mediterranean Journal of Social Sciences, 2011)
In today’s competitive environment Human Resource Management has become a valuable part of each organization especially for banks because HRM policies are directly linked with the overall performance. The main purpose of the paper is to study the recruitment and retention policies implied by the public sector of Pakistan. By deep analysis of problems and challenges study suggest the implementation of various policies to become an employer of choice. Previous studies on recruitment and retention have been performed mainly in western context. The distinction of this paper is that it studies recruitment and retention practices merely in public sector of Pakistan. The paper proposes a conceptual framework linking various psychological factors and strategic HRM perspectives, examining how various strategies adopted by firms help in image building and recruiting and retaining talented employees. Hypotheses were developed with the help of framework. The study was conducted in 20 branches of NBP in Faisalabad and a sample size of 100 was selected. Five point likert scales were used to get the responses. Mean and standard deviation were calculated to know the relationships o variables and at last bi variate test was applied to conclude.